Roles of Atmosphere Thermodynamic and Ocean Dynamic Processes on the Upward Trend of Summer Marine Heatwaves Occurrence in East Asian Marginal Seas - Lee, Sang-Bin; Yeh, Sang-Wook; Lee, Jeong-Seo; Park, Young-Gyu; Kwon, Minho; Jun, Sang-Yoon; Jo, Hyun-Su (Frontiers in Marine Science, 2022)
By analyzing the European Centre for Medium-Range Weather Forecasts reanalysis version 5 (ERA5) dataset, we found increased frequency of marine heatwaves (MHWs) in East Asian marginal seas (EAMS) during the boreal summer (June-July-August) in the recent past. To examine which processes are responsible for the upward trend of MHW occurrence, we performed three numerical simulations using Modular Ocean Model version 5 (MOM5) forced by ERA5 dataset. The first experiment used historical atmospheric variables to force the MOM5 for 1982 to 2020, which reasonably simulated the upward trend of MHWs as well as its dominant variability in terms of temporal and spatial structure in EAMS. The second (third) experiment is the same as in the first except that the atmosphere variables used to force the MOM5 consisted of thermodynamic (dynamic) variables only. The upward trend of MHW occurrence in EAMS is simulated in the first and the second experiment only. We argue that the atmosphere thermodynamic processes, in particular, the shortwave radiative forcing, play a key role in inducing the upward trend of MHW occurrence in EAMS during the boreal summer compared to the ocean dynamic processes.